Are open-identity donors prepared for release of their identity? Long-term follow-up of a national sample of oocyte and sperm donors - Lampic, Claudia; Thorup, Emilia; Bladh, Marie; Nedstrand, Elizabeth; Brinck, Xana; Svanberg, Agneta Skoog; Sydsjö, Gunilla (Human Reproduction, 2025)
STUDY QUESTION What are the perspectives of oocyte and sperm donors 14-17 years post-donation on the release of their identity and potential contact with donor-conceived offspring (DCO)? SUMMARY ANSWER Most oocyte and sperm donors wanted to be notified about future releases of their identity and were positive towards contact with DCO, but more than half expressed a need for support in relation to potential contact. WHAT IS KNOWN ALREADY Worldwide, an increasing number of individuals conceived by open-identity donation are reaching an age where they may request donor identity. Little is known regarding donors' preparedness for identity-release and potential contact with DCO. STUDY DESIGN, SIZE, DURATION This study is part of the 'Swedish Study on Gamete Donation' (SSGD), a longitudinal multicentre study including oocyte and sperm donors at all clinics performing gamete donation in Sweden. Consecutive recruitment during a 3-year period (2005-2008) resulted in an initial sample of 299 donors (80% response rate). The present study concerns the fifth wave of data collection of the SSGD conducted 14-17 years post-donation, with very high response rates (oocyte donor 83%, sperm donor 92%). Following exclusion of donors who knew the recipients and/or knew that the donation had not resulted in a living child, the final sample comprised 100 oocyte donor and 91 sperm donor. PARTICIPANTS/MATERIALS, SETTING, METHODS Fourteen to seventeen years after having participated in open-identity donation of their gametes, participants completed a postal survey with study-specific questions. Questions concerned preferences related to the release of their identity to DCO, attitudes towards future contact with people conceived from their donations, need for support regarding potential contact, attitudes towards the perceived importance of the genetic link between parent and child, and openness about having donated oocytes or sperm. Chi-square tests, independent t-tests, and Mann-Whitney U-tests were used to compare responses between oocyte and sperm donors. Multinomial logistic regression was used to identify factors associated with donors' attitudes towards future contact with DCO and need for support. Content analysis was used to analyse free-text responses. MAIN RESULTS AND THE ROLE OF CHANCE Almost all oocyte and sperm donors wanted to be notified about requests for their identity (93%). A majority had positive (71%) or neutral (19%) attitudes towards contact with DCO, but a small group was negative (10%), and more than half wanted support related to potential contact (59%). Free-text responses indicated that donors took the interests of both the DCO and their own family members into account when considering future contact. Donors' attitudes towards contact with people conceived from their donations and donors' need for support were not predicted by socio-demographic factors such as donors' gender and legal children, nor by the perceived importance of the genetic parent-child link. While oocyte and sperm donors displayed similar perspectives on most outcomes, oocyte donors were found to be more open about having donated to all people except partners (All P-values <0.05) and sperm donors placed a higher value on the genetic parent-child link (P = 0.005). LIMITATIONS, REASONS FOR CAUTION While the multicentre design and high response rates strengthen the external validity of our findings, the results may not be generalizable to originally anonymous donors. The scope of the qualitative analysis was limited due to the restricted number of free-text responses. An interview format may be needed to further explore donors' thoughts and feelings regarding potential contact with DCO. WIDER IMPLICATIONS OF THE FINDINGS At a time when increasing numbers of donor-conceived people can request donor-identifying information, our finding that donors generally are positive or neutral towards being contacted by DCO is encouraging. Long-term support of open-identity donors should include notification about requests for their identity and access to counselling and information about handling potential future contact with people conceived from their donations.
Keywords: donor conception; donor preferences; genetic link; identity-release; post-donation contact; support needs